Aneurysms of the superficial venous system: classification and treatment - Ronald G. Bush; Peggy Bush (Veins and Lymphatics, 2014)
Superficial venous aneurysms are rarely described and they may remain indolent or become the source for pulmonary emboli. A system of classification and treatment protocol according to size and location is proposed. Three hundred thirty patients were evaluated for symptomatic venous disease (C2-C6) over a 2-year period. A proposed designation for venous aneurysm is described. Patients fulfilling this criterion are described in reference to site of involvement, histologic findings, and method of treatment. Five percent of patients met the criteria for venous aneurysm. Nine aneurysms of the greater saphenous vein were identified. Three aneurysms were proximal to the subterminal valve and the rest were distal. Six aneurysms of the anterior accessory greater saphenous vein (AAGSV) were identified. Three aneurysms of the AAGSV spontaneously thrombosed. Two patients presented with aneurysms of the small saphenous vein. Histology revealed thickened intima, smooth muscle and adventitia. Aneurysm designation relates to diameter of normal and contiguous vein. All superficial venous aneurysms in close proximity to the junction of the femoral or popliteal vein should be ligated. Classification of venous aneurysms should include the AAGSV, which may present with spontaneous thrombosis.